Screening of the glucocerebrosidase (GBA) gene in South Africans of African ancestry with Parkinson’s disease - Mahungu, Amokelani C. (Neurobiol Aging, 2019)
Sequence variants in glucocerebrosidase (GBA) are a major genetic risk factor for Parkinson’s disease (PD), and display ethnic-dependent frequencies, e.g. variants such as p.N370S and 84insGG are common in Ashkenazi Jewish patients. Notably, there are limited studies on Black patients from the African continent; hence, we conducted a study on 30 South African Black PD patients. All 11 exons of GBA were screened using a nested PCR approach to avoid pseudogene contamination. We identified previously described Gaucher’s disease-associated variants, p.R120W in one patient [age-at-onset (AAO) of 35 years], and p.R131L in another patient (AAO 3O years) and in her affected sibling (AAO 45 years). Also, we found three previously-identified [p.K(−27)R, p.T36del, and p.Q497*], and two novel (p.F216L and p.G478R) variants. Screening of ethnic-matched controls for the novel variants revealed that the allele frequency of p.F216L was 9.9%, whereas p.G478R was not found in the controls. Studies such as these are important and necessary to reveal the genetic architecture underlying PD in the understudied patients of African ancestry.